2019
DOI: 10.2174/0929867324666170523125806
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition as a Health Determinant in Elderly Patients

Abstract: An adequate caloric intake is a major determinant for the health status especially when degenerative conditions become a predominant risk for difficult-to-treat diseases as in aging. The maintenance of the nutritional status is the best measure to counteract the risk of protein-caloric malnutrition and its complications which often sneakily affects elderly population and in particular frail patients. Both organic and social risk factors [economic hardship, loneliness, institutionalization] are important as det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…Nutrition plays an important role in the normal physiological functions of the human body and treatment of diseases especially in elderly patients (19,20). Currently, a variety of nutritional status evaluation tools, including Nutritional Risk Screening 2002, Nutrition Risk in the Critically Ill, GNRI, are available (21-23).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition plays an important role in the normal physiological functions of the human body and treatment of diseases especially in elderly patients (19,20). Currently, a variety of nutritional status evaluation tools, including Nutritional Risk Screening 2002, Nutrition Risk in the Critically Ill, GNRI, are available (21-23).…”
Section: Discussionmentioning
confidence: 99%
“…Diet is a major modifiable determinant of chronic diseases and there is a large body of evidence showing that modifications to improve diet quality are directly associated with health benefits [ 13 ]. Diet is a topic of interest for people with RA and many have reported that certain foods can help alleviate symptoms and other foods may trigger ‘flare-ups’ leading to swelling, pain and stiffness [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of RA remains unclear; genetic predisposition represents a great percentage of risk while the remainder is thought to be connected to modifiable factors such as tobacco smoking, diet and exercise [10]. Diet is a major modifiable determinant of chronic conditions with a large body of evidence showing that modifications to improve diet quality are directly associated with health benefits [11]. Diet is an area of interest for people living with RA as a way of improving symptoms [12].…”
Section: Introductionmentioning
confidence: 99%